2013
DOI: 10.1371/journal.pone.0076246
|View full text |Cite
|
Sign up to set email alerts
|

The Sicker Sex: Understanding Male Biases in Parasitic Infection, Resource Allocation and Fitness

Abstract: The “sicker sex” idea summarizes our knowledge of sex biases in parasite burden and immune ability whereby males fare worse than females. The theoretical basis of this is that because males invest more on mating effort than females, the former pay the costs by having a weaker immune system and thus being more susceptible to parasites. Females, conversely, have a greater parental investment. Here we tested the following: a) whether both sexes differ in their ability to defend against parasites using a natural h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 58 publications
(92 reference statements)
1
38
1
1
Order By: Relevance
“…Age group 2 (mature) used for this study. See Córdoba‐Aguilar and Munguía‐Steyer () for further details.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Age group 2 (mature) used for this study. See Córdoba‐Aguilar and Munguía‐Steyer () for further details.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the vast majority of host species do not have a sex bias and the ones that do, represent both sexes at an almost equal number. An exception, and a study worth noticing, was done by Córdoba‐Aguilar and Munguía‐Steyer (). They studied damselflies with gregarine and water mite parasites both in the field and in a laboratory experiment and found that males harbor more parasites than females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common pattern among mammals is higher infection levels in males compared to females (Schalk and Forbes 1997, C ordoba-Aguilar and Mungu ıa-Steyer 2013, Metcalf and Graham 2018 and in the young and senescent compared to prime-aged individuals (Hayward et al 2011, Abolins et al 2018, Benton et al 2018. Physiological and behavioral differences are expected to be major drivers of the skewed appearance of many diseases (Guerra-Silveira and Abad-Franch 2013).…”
Section: Introductionmentioning
confidence: 99%